Comparative Study between Topical Metformin 30% Cream and Topical Adapalene 0.1 % Cream in The Treatment of Acanthosis Nigricans [Clinicodermoscopic Study] - Sabrean Elkhodary; Rabie Atallah; Hany Aboelwafa (International Journal of Medical Arts, 2023)
Background: Acanthosis nigricans [AN] is a common cutaneous disorder with multiple etiologies. For cosmetic purposes, dermatologists usually recommend topical keratolytics, laser treatments, or chemical peels. The treatment of AN with a topical retinoid called adapalene has a high rate of success. Metformin, an insulin sensitizer, was proposed as a therapy option for AN by focusing on the insulin resistance connected to AN.Aim of the work: This study was done to compare the efficacy and safety of topical 30% metformin cream with topical 0.1 adapalene cream.Patients and Methods: There were 40 instances of AN in the most recent study. Two sets of cases, each with 20 patients, were randomly assigned: Group A [the metformin group] and Group B [the adapalene group]. The patients had a thorough dermatological examination along with a general clinical evaluation. The initial assessment included the calculation of HOMA-IR, assessment of disease severity, digital photographs, and dermoscopic assessment. After completion of treatment, clinical response and the degree of improvement were determined in the cases within the two groups. Follow-up was done for 2 months after treatment.Results: All clinical and dermoscopic results evaluated following treatment show statistically significant variance across the tested groups in terms of the degree of improvement. In the adapalene group, the extent of improvement was greater. The mean ANASI score for the metformin group decreased from 32.4 to 27.8 pre- and post-operatively, while for the adapalene group, it decreased from 26.8 to 18.4. The Adapalene group had a larger percent change, although there is no statistically significant distinction between them.Conclusion: Adapalene 0.1% cream was more successful than Metformin 30% cream in treating acanthosis nigricans with minimal and tolerable side effects. There was no difference between the two therapy regimens in terms of the chance of recurrence.